Managing Supply Chains on the Silk Road : Strategy, Performance, and Risk. - Haksoz, Cagri (CRC Press, 2011)
This book present emerging supply chain practices from the Silk Road regions that include China, Hong Kong, India, Pakistan, Iran, Central Asia, Lebanon, Turkey, Israel, and Hungary. It takes a results-oriented, comparative approach to supply chain management covering structural, strategic, and operational topics. Providing insights for assessing performance and hedging risk, this is a handbook that no competitive supply chain executive can afford to ignore.